2005
DOI: 10.1557/jmr.2005.0328
|View full text |Cite
|
Sign up to set email alerts
|

Vickers hardness and compressive properties of bulk metallic glasses and nanostructure-dendrite composites

Abstract: The compressive properties and the Vickers hardness of Cu-, Fe-, Mg-, and Zr-based monolithic bulk metallic glasses (BMGs) as well as Ti-based nanostructure-dendrite composites were investigated and compared. The monolithic BMGs exhibit nearly the same yield strength σ y and fracture strength σf but poor plasticity. The Vickers hardness HV of the monolithic BMGs follows the empirical relationship HV/3 ≈σy ≈σf. The Ti-based composites yield at a relatively low stress level (less than 850 MPa) but fail at a very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The elastic energy density of one serration event, δ, can be calculated by δ = σ ε/2, where σ and ε are the elastic stress and strain in one serration event, respectively. 53 As the SBs start to propagate, the elastic energy of the serration events is consumed by the initiation and propagation of SBs in the local plastic region, i.e. configurational hopping of STZs.…”
Section: Copyright 2013 Author(s) All Article Content Except Where mentioning
confidence: 99%
“…The elastic energy density of one serration event, δ, can be calculated by δ = σ ε/2, where σ and ε are the elastic stress and strain in one serration event, respectively. 53 As the SBs start to propagate, the elastic energy of the serration events is consumed by the initiation and propagation of SBs in the local plastic region, i.e. configurational hopping of STZs.…”
Section: Copyright 2013 Author(s) All Article Content Except Where mentioning
confidence: 99%
“…The strain-energy density of one serration event (Dd) is Dd ¼ 1 2 DrDe, here Dr and De are the variable quantities of the stress and strain in one serration event, respectively, [29,43] as presented in the inset of Figure 1(a). Considering that the plastic strain results in a drift of the strain-energy-density value, a normalization of the strainenergy density is carried out to eliminate the statistical error.…”
Section: B Soc Behaviormentioning
confidence: 99%
“…A sequence of serration events indicates the aggregation and release of deformation energy during plastic deformation, which manifests itself as discrete bursts of plasticity. [30] The so-called shear avalanches of a sudden stress drop can force the sample to selforganize into a critical state. [31] To further characterize the plastic flow behavior of the present alloys, a statistical analysis of the serration events was conducted.…”
Section: Resultsmentioning
confidence: 99%
“…[30] Dd provides a parameter reflecting the dynamics of shear deformation in BMGs, and to further characterize plastic flow, we plot the elastic energy density distribution, which was obtained from all serrations occurring during plastic flow (Figure 2(b)). It has been suggested that the cumulative probability distribution follows a power law, [32] according to the following equation: …”
Section: Resultsmentioning
confidence: 99%